Bacterial and eukaryotic biodiversity patterns in terrestrial and aquatic habitats in the Sør Rondane Mountains, Dronning Maud Land, East Antarctica - Obbels, Dagmar; Verleyen, Elie; Mano, Marie-José; Namsaraev, Zorigto; Sweetlove, Maxime; Tytgat, Bjorn; Fernandez-Carazo, Rafael; De Wever, Aaike; D'hondt, Sofie; Ertz, Damien; Elster, Josef; Sabbe, Koen; et al. (FEMS microbiology ecology, 2016)
The bacterial and microeukaryotic biodiversity were studied using pyrosequencing analysis on a 454 GS FLX+ platform of partial SSU rRNA genes in terrestrial and aquatic habitats of the Sør Rondane Mountains, including soils, on mosses, endolithic communities, cryoconite holes and supraglacial and subglacial meltwater lenses. This inventory was complemented with Denaturing Gradient Gel Electrophoresis targeting Chlorophyta and Cyanobacteria. OTUs belonging to the Rotifera, Chlorophyta, Tardigrada, Ciliophora, Cercozoa, Fungi, Bryophyta, Bacillariophyta, Collembola and Nematoda were present with a relative abundance of at least 0.1% in the eukaryotic communities. Cyanobacteria, Proteobacteria, Bacteroidetes, Acidobacteria, FBP and Actinobacteria were the most abundant bacterial phyla. Multivariate analyses of the pyrosequencing data revealed a general lack of differentiation of both eukaryotes and prokaryotes according to habitat type. However, the bacterial community structure in the aquatic habitats was dominated by the filamentous cyanobacteria Leptolyngbya and appeared to be significantly different compared with those in dry soils, on mosses, and in endolithic habitats. A striking feature in all datasets was the detection of a relatively large amount of sequences new to science, which underscores the need for additional biodiversity assessments in Antarctic inland locations.
Keywords: houby; Sequence Analysis, DNA; Soil Microbiology; Acidobacteria; ekosystém; sinice; biodiverzita; denaturační gradientová gelová elektroforéza; Cyanobacteria; Bacteroidetes; Fungi; Proteobacteria; Antarctic Regions; Actinobacteria; Base Sequence; sekvence nukleotidů; Soil; půdní mikrobiologie; sekvenční analýza DNA; Biodiversity; Antarktida; RNA ribozomální; Ecosystem; RNA, Ribosomal; půda; Denaturing Gradient Gel Electrophoresis; Chlorophyta